Guidance and Counseling Management Implementation Pattern at MAN Karimun Indonesia - Noperlis, Anggi Dwi; Firman, Firman; Neviyarni, Neviyarni; Che Amat, Muhammad Asyraf Bin (Universitas Mathla'ul Anwar Banten, 2023)
Management is an effort to achieve goals through individual cooperation with groups through the support of other sources or facilities. In management there are 5 management functions namely Planning, Organizing, Actuating and Controlling which is commonly called POAC. If POAC is implemented optimally, effective guidance and counseling services will be created. At MAN Karimun the implementation of guidance and counseling management is still experiencing several obstacles so that good and effective guidance and counseling management is needed. The purpose of this study was to find out about the pattern of implementation of guidance and counseling services at MAN Karimun. This research method uses a qualitative descriptive method. Research location in MAN Karimun. The research informants were 1 guidance counseling teacher and 1 school principal. Data collection techniques through interviews. The results of the study show that in the implementation of guidance and counseling management for guidance counseling teachers there are organizations from school members such as school principals, homeroom teachers, subject teachers, and administration. This service is carried out according to the needs of students. The guidance and counseling activities format used is individual and classical. Counseling guidance at MAN Karimun is also supervised.